The applicability of mineral and mining rights concepts in facilitating value capture in South Africa - van Heerden, Chrisjan (Department of Construction Economics and Management, 2017)
South Africa needs additional funds for public infrastructure investment. Value Capture could potentially be implemented as a mechanism to raise additional funding. Value Capture depends on maximising land value. Ownership constraints to land development prevent land value from being maximised. The study uses doctrinal legal research to investigate how the principles found in South African mineral rights legislation overcome ownership constraints to developing mineral rich land to its highest and best use. The study also investigates how these mineral rights principles could be applied to land in general, in order to overcome ownership constraints to development. Within this context the study demonstrates how land might be expropriated for development purposes, and how such expropriation could create opportunities for Value Capture.